The significance of understanding the fair play principle for the development of social competences among youth - Bronikowska, Małgorzata; Ludwiczak, Mateusz (Physical education, sport and olympism from a pedagogical perspective, 2023)
This article examines prosocial behaviours and the perception of understanding fair play rule as a principle in the context of physical education and sport in adolescents participating in sports, and those not undertaking sports at all. The main aim of this research is to explore and indicate potential connections between understanding of the idea of fair play and selected prosocial behaviours (e.g., abiding by the rules, respecting decisions of the referee and sportsmanship) in youth. In total, 1257 secondary school students, aged 16.1 ± 0.87 years (627 girls and 600 boys), were interviewed. For assessing the level of fair play awareness (P), the Fair Play Moral Dimensions Concept Scale was used. To measure the confirmed level of prosocial behaviours of school students, the survey My Physical Education Class was used.Participants were divided into groups based on their training experience (no sports at all, amateur sports enthusiast, professional sports athlete). Then subgroups according to their understanding of the Fair Play principle (P1 to P3) were designed The results show significant differences in all dilemmas in various groups in relation to scores in subgroup P3 (p = 0.056; p = 0.012; p = 0.003) regarding subgroups P2 and P1 in the level of understanding fair play. Overall, the percentage of respondents who view fair play rule only in the context of sport (P1) is 69%. Far fewer (31%) are those who understand it more broadly as a principle that applies to everyday life situations (P3). Therefore we state that it is crucial to promote moral development during Physical education and sports process, especially the value of respect. For that reason, we need well educated PE teachers and sport couches.